2022
DOI: 10.1186/s12890-022-01933-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new developed disposable and portable bronchoscopy system

Abstract: Background Bronchoscopy is critical in the treatment of patients with coronavirus disease (COVID-19), and its use is associated with the challenges of stringent sterilization and virus transmission risk. We developed a disposable and portable bronchoscope (YunSendo-R) and compared its safety and function with those of current reusable and single-use bronchoscopes using an animal model. Methods We compared the YunSendo-R system with a commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 27 An animal study using a new system not commercially available reported advantages over a similar reusable Ambu ® aScope3™ scope. 28 All companies have a slim scope option with other some differences in other size available. We elected the larger 2.8 mm channel scope (3 mm Pentax SUFB) as this is more optimal for suction.…”
Section: Discussionmentioning
confidence: 99%
“… 27 An animal study using a new system not commercially available reported advantages over a similar reusable Ambu ® aScope3™ scope. 28 All companies have a slim scope option with other some differences in other size available. We elected the larger 2.8 mm channel scope (3 mm Pentax SUFB) as this is more optimal for suction.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of performance comparison, Liang et al found that the YunSendo-R(SFBs) is superior to the Ambu aScope3 (SFBs) in terms of image clarity, color contrast, and illumination [ 27 ]. And it had similar vision and operability to the Olympus bronchoscope (RFBs).…”
Section: Discussionmentioning
confidence: 99%